Аналіз плазмонних резонансів металевої нанотрубки з подвійною оболонкою - Пшонкіна, А. С. (ХНУРЕ, 2023)
Typical problem of electrodynamics that based on effective analyticalnumerical investigation of stationary fields in systems of two-dimensional structure has been solved. Isolated metal nanoshell with double shell were studied. All the possible plasmons of configuration of «nanomatryoshka» (or concentric nanoshell) has been described and classified. Corresponding equations for detennining the complex eigenvalues has been obtained. Field distributions in the near-field, their frequency and quality factor (Q) has been considered